Water Geochemistry and Stable Isotope Changes Record Groundwater Mixing After a Regional Earthquake in Northeast India - Sourav Kumar; Michael Manga; Archana M. Nair; Abhishek Dixit; Chandan Mahanta (Geochemistry, Geophysics, Geosystems)
Abstract Recorded earthquake‐induced changes in hydrogeological systems date back over 2,000 years. As a part of our ongoing hydrogeochemical monitoring effort to study such changes, we collected 406 groundwater samples twice a week between February 2021 and July 2023 from two bore wells in the Kopili fault zone of Northeast India. We analyzed stable isotope ratios (δ2H, δ18O) and dissolved element concentrations to obtain a 2.5‐year hydrogeochemical time series and responses to multiple regional earthquakes (Mw ≥ 3) within the monitored period. We find significant but transient anomalies in both the chemical and isotopic composition of groundwater at one of the observation wells (OW1) after the 2021 Assam Mw 6.4 earthquake, followed by prolonged alterations in the hydrochemistry at both wells. We do not identify any precursory changes. Using multivariate statistical techniques and analyzing compositional changes before and after the mainshock, we infer that the hydrochemical anomalies at OW1, representing an immediate response to the mainshock, can be attributed to the potential breach of a hydrological barrier. This, in turn, allowed the infiltration of new water into the OW1 aquifer, potentially sourced from the nearby Brahmaputra River. Subsequently, during the post‐anomaly period, the earthquake‐induced fracturing and the associated changes in permeability sustained a prolonged period of mixing between surface water and groundwater, resulting in newly formed hydrochemistry at both wells. Our findings highlight the dynamic nature of aquifer properties during earthquakes. Long‐term continuous evaluation of such changes may provide new insights into feedback between tectonics and fluid flow in the crust.